Village Government Strategy in Local Economic Empowerment and Community Welfare: An Empirical Study in Sungai Duren Village - Dinda Rosanti Salsa Bela (Civic Governance and Public Administration, 2026)
This study aims to analyze the strategy of the Sungai Duren Village Government in improving community welfare through optimizing the food security sector and diversifying the productive economy. This study uses a qualitative research method with data collection techniques including interviews, field observations, and documentation analysis. Research informants were determined purposively, consisting of the village government, micro-entrepreneurs, tilapia fish cage managers, and community beneficiaries of the program. Data analysis was carried out interactively through the stages of data reduction, data presentation, and conclusion drawing. The results show that the village government's strategy is articulated into four pillars: strengthening food security based on tilapia fish cages, downstreaming processed fishery MSME products, poverty mitigation through Village Fund Direct Cash Assistance (BLT), and projections of microfinance institutions through the Merah Putih Village Cooperative. The village government acts as a facilitator and dynamic agent of multi-actor collaboration (collaborative governance) with the academic and private sectors. However, the sustainability of the program is still hampered by ecological vulnerability in the form of water pollution, limited village fiscal capacity, and low community technological literacy. This study recommends the need to strengthen local environmental protection regulations and strengthen the managerial capacity of village economic institutions in a structured manner